Continuous spinal anaesthesia with minimally invasive haemodynamic monitoring for surgical hip repair in two patients with severe aortic stenosis - López,María Mercedes (2016)
BACKGROUND AND OBJECTIVES: Aortic stenosis increases perioperative morbidity and mortality, perioperative invasive monitoring is advised for patients with an aortic valve area <1.0 cm2 or a mean aortic valve gradient >30 mm Hg and it is important to avoid hypotension and arrhythmias. We report the anaesthetic management with continuous spinal anaesthesia and minimally invasive haemodynamic monitoring of two patients with severe aortic stenosis undergoing surgical hip repair. CASE REPORT: Two women with severe aortic stenosis were scheduled for hip fracture repair. Continuous spinal anaesthesia with minimally invasive haemodynamic monitoring was used for anaesthetic management of both. Surgery was performed successfully after two consecutive doses of 2 mg of isobaric bupivacaine 0.5% in one of them and four consecutive doses in the other. Haemodynamic conditions remained stable throughout the intervention. Vital signs and haemodynamic parameters remained stable throughout the two interventions. CONCLUSION: Our report illustrates the use of continuous spinal anaesthesia with minimally invasive haemodynamic monitoring as a valid alternative to general or epidural anaesthesia in two patients with severe aortic stenosis who are undergoing lower limb surgery. However, controlled clinical trials would be required to establish that this technique is safe and effective in these type or patients.